Behavioral Biases in Managerial Decision-Making: Implications for Cost Control and Budgeting - Krishnakumari , Dr.S.; Pattanaik, Ashutosh; Cajla, Pancham; Kandhari, Harsimrat; Rashmi; Hafiz, Dr. Ansari Mehrunnisa; Samantaray, Dr. Alaka (International Journal of Accounting and Economics Studies, 2025)
The term "decision" has been derived from the Latin word "decidere': to cut off. A decision is a settlement, a fixed resolve ending result, a judgment, and a resolution. Decision-making has been defined as the selection of a course of action out of alternatives; it is at the very core of planning. Managers sometimes consider decision-making their core job since they must constantly decide what is to be done, by whom, when, where, and sometimes even how it is to be done. Decision-making is a Human Mental Process. Rationality is injected through the human brain, which has the capacity of learning, think, and relate intricate facts and variables while deciding. Decision making is rational in the sense, the manager decides by choosing and judging the alternatives to attain desired goals by choosing the most desired one. Individuals acting or deciding rationally are trying to attain some goal that cannot be reached without action. In most cases, not all alternatives can be examined, even with the most advanced available techniques of analysis and computers. A decision is an option between numerous alternatives, and a decision maker is the person making such an option. Although decisions can be arrived at instantly, more often the process of identification, analysis, assessment, choice, and planning is the process in decision-making. Strategy, as a word, is associated with Military science. A policy u when a specific meaning is given under a dominating situation, and in consideration of the enemy or competition policy, becomes a strategy.